A mixed integer linear programming model for dynamic supplier and carrier selection problems. (6th May 2019) - Wicaksono, Purnawan Adi; Pujawan, I. Nyoman; Widodo, Erwin
The dynamic supplier selection problem (DSSP), which occurs when no supplier can fulfil the buyer's total demand due to various limitations, has received attention from academics. However, to the best of our knowledge, there is no publication that addresses the DSSP and carrier selection simultaneously. Given that products are sourced from different suppliers, the choice of carrier is important in order to satisfy demand at the minimum total cost. In this paper, we present a model that integrates the DSSP and carrier selection under uncertain delivery performance; that is, a portion of orders are not delivered on time and a portion of delivered goods are imperfect and hence are rejected by the buyer. We propose a mixed integer linear programming (MILP) model and apply it to a case where a buyer is sourcing multiple items from multiple suppliers and the decision has to be made on a multi-period planning horizon. A numerical example has been tested to show the effectiveness of the model. We assume that backlogging is allowed and the effect of demand fluctuation is analysed.